PENGEMBANGAN LEMBAR KERJA PESERTA DIDIKBERBASIS MULTIPLEINTELLIGENCESKELAS XISMA NEGERI 8 PADANG - YUANDA ELSA ZAHARA (Departemen Matematika, 2021)
The purpose of this LKPD development research is to prepare student worksheets based on valid and practical multiple intelligences for senior high school class XI. This research is a development research using the plomp step which consists of three stages, namely: the preliminary research stage, the prototype making stage, and the assessment stage. Based on the results of the validation of student worksheets in terms of four aspects, namely: content feasibility, linguistic aspects, presentation aspects, and typography aspects, it shows that multiple intelligence-based student worksheets have a validity level of 77.38% with the valid category. In the practicality category of the student worksheets, seen from the responses of three students who had done the one to one evaluation stage, it was 80.83% with the practical category. Based on these results it can be concluded that multiple intelligence-based student worksheets can be declared valid and practical. Keywords—development research, student worksheets, multiple intelligence